Case’s Method for Anlı-Güngör Scattering Formula - R. Gökhan Türeci; Ahmet Bülbül (Süleyman Demirel Üniversitesi Fen-Edebiyat Fakültesi Fen Dergisi, 2022)
Case method is a powerful method in solving one-speed neutron transport equation. The method can be applied to one-speed neutron transport problems and pseudo- geometry problems. The method basis on the usage of Case’s eigenfunctions and the orthogonality relations with the certain boundary conditions according to the interested problem. The scattering effects can be investigated via Mika scattering formula and also İnönü’s scattering formula. In this study Case method’s formalism is derived by using Anlı-Güngör scattering formula as an analogue of Mika’s scattering function. This study is about the Case’s eigenfunctions, normalization relation and the orthogonality properties among these eigenfunctions and, moreover; Case’s eigenfunctions and the orthogonality properties must be rewritten according to the studied scattering order as the number of scattering order increase in Anlı-Güngör scattering formula.